Drug handling in a paediatric intensive care unit: can errors be prevented by a three-step intervention? - Niemann, Dorothee; Bertsche, Astrid; Meyrath, David; Oelsner, S.; Ewen, A. L.; Pickardt, Björn von; Henhapl, T.; Hoffmann, Georg F.; Meyburg, Jochen; Bertsche, Thilo (Klinische Pädiatrie, 2014)
Drug handling in paediatric intensive care units (PICU) is prone to medication errors. We aimed to identify type and prevalence of those errors and to assess preventative interventions. Prospective intervention study investigating a 3-step intervention for preventing errors in drug handling in a 10-bed PICU of a university hospital. Nurses’ drug handling was monitored in daily routine to identify the number of patients affected by errors and overall prevalence and types of errors in drug handling. We implemented a comprehensive intervention consisting of an information handout, a training course, and a 76-page reference book tailored to reduce the prevalence. The prevalence of errors in drug handling decreased from 83% (555 errors/668 processes) to 63% (554/883; p<0.001) after the intervention. The number of affected patients remained unchanged (95% vs. 89%, p=0.370). Peroral (PO) drugs (1.33 errors/process) were more error-prone than intravenous (IV) drugs (0.64), despite being used less frequently (27% vs. 73% of all processes, p<0.001). The interventions decreased the prevalence to 0.77 errors/process (p<0.001) in PO and to 0.52 in IV drugs (p=0.025). Errors in drug handling were alarmingly frequent. PO drugs were frequently subject to errors, even though being used less frequently. The implementation of a comprehensive intervention succeeded in reducing the prevalence of errors. Yet further refinements are necessary to decrease also the number of affected patients.